Prevalência e fatores associados ao risco de quedas em idosos do município de Cuiabá-MT - Regis, Juari José (2016)
Nowadays, fall is a matter of worldwide public health, generating social impact, especially in developing cxountries (BRAZIL) by the high cost provided by it. Besides lesions and fractures, sequels remain for life, such as: reduction of functional capability, depression, low self-esteem and social isolation. This study had the goal to identify the prevalence and factors associated to the risk of falls amond the elderly from Cuiabá-MT. The sample was composed of 387 senior citizens, aged 65 or more, both sexes, living in Cuiabá-MT, assessed from March 2009 to March 2010, by socioeconomical questionnaire, self- related questionnaire on falls (history), daily life instrumental activities, self efficacy for fall (FESI), perceived physical health, functional capability assessment and nutritional state, anthropometric measures, short physical performance battery (SPPB) and physical tests (palmar prehension and unipodal balance). Prevalences and percentages of the senior citizens' sociodemographic, as well as fall history, were calculated. To assess the association between fall with the other qualitative variables, it was held the non- parametric test of Qui-Quadrado, with 95% of significance. When the expected frequencies of Qui-Quadrado test presented expected value smaller than 5, Fisher exact test was used, with significance level of 95%. For association between falls with the other quantitative variables, it was used the non-parametric test of Wilcox and Mann-Whitney, laso with significance level of 95%. By mens of statistical analysis, it was stated that only 16% of the elderly have fallen on the last year, being that females are 2,09 times more likely to fall, the ones aged over 75 have 1,87 times more risk of fall. Regarding physical tests, only the left unipodal balance had no association with falls. It can be concluded that there are many vatiables associated to the risk of falls, making it harder for preventive work, still prevalence increases with age and reaches mainly females. Considering this, the practice of physical exercise becomes the best tool to modulate the changes occurred with the aging process. Still, accessibility technical norms need to be complied in order to reduce isolation, the risks of falls and grave outcomes such as death in elderly population.